Design and Fabrication of Typical Pipe Cutting Machine - Balashanmugam, P.; Balasubramanian, G. (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
The Machine we designed and fabricated is used for cutting any shape of object like Circular, Rectangular, and Polygon. Hence our project namely Typical Pipe Cutting Machine is a Special type of Machine. According to the type of material to be cut, the cutting tool can be changed. This project gives details of Cutting various shapes and sizes of components. This machine can be widely applied in almost all type of industries. The pipe cutting process is a main part of the all industries. Normally the cutting machine is manually hand operated one for medium and small scale industries. In our project is pneumatically operated “TYPICAL PIPE CUTTING MACHINE”. Automation in the modern world is inevitable. Any automatic machine aimed at the economical use of man, machine, and material worth the most. In our project is hand operated D.C valve and flow control valve is used for semi-automation. The pipe cutting machine works with the help of pneumatic double acting cylinder. The piston is connected to the moving cutting tool. It is also used to cut the small size of sheet metal. The machine is portable in size, so easy transportable.